Probabilistic seismic hazard analysis of Moldova and adjacent territories - R. Burtiev (Геофизический журнал, 2015)
A new approach to seismic hazard assessment is proposed. It means that in a certain location of the Earth’s surface during the time t will occurs a certain number n of shakes and m of them with intensity Ik. The algorithm of seismic hazard estimation in terms of macroseismic scale and "EUROCODE 8" standard are elaborated. The cluster analysis has identified in Romania 13 seismic zones. For define the distribution of earthquakes parameters the Markov model of identified seismic zones seismicity is constructed. The PSHA of Bulgaria, Romania and Moldova territories on the basis of ROMPLUS catalogue is carried out.